ESCHATOLOGY AS A RELIGIOUS-MYTHOLOGICAL PHENOMENON IN PHILOSOPHY AND LITERATURE - Tatyana Djalalitdinovna Polatova (Galaxy International Interdisciplinary Research Journal, 2023)
The article deals with eschatology as a religious and mythological phenomenon in philosophy and literature.